Post-Merger Changes in Public Sector Banks : A Case of National Bank Ltd. and Bank of Gujarat Ltd. - Mainrai, Girish; Mohania, Sarvesh (Prabandhan: Indian Journal of Management, 2020)
Organizations adopt a number of strategies for ensuring their growth and even survival according to changes in the business environment. Mergers and acquisitions are very common in any sector, the underlying motives for which may vary depending upon the situations confronted by the entities involved. The strategic decisions mentioned above have a profound impact on the HR (human resource) of the organization. Mergers may lead to loss of identity for one or more entities, impacting not only working, but emotions and feelings of their employees also. The present case relates to the merger of Bank of Gujarat into National Bank as per the government’s directive. The employees of Bank of Gujarat faced new challenges in terms of learning new policies and procedures and unlearning their old ones at the same time. The other hurdle, which they never imagined that they will face, was of stepmotherly treatment by the management of the merged entity. The employees were facing hardships in transfers, placement, promotion, and other HR decisions. This led to widespread dissatisfaction among the employees of Bank of Gujarat, impacting the morale of the employees.